DETERMINANTS OF STRESS RECOGNITION AND JOB SATISFACTION IN HOSPITALS FOR HEALTH PROFESSIONALS IN INDONESIA - Suryo Wibowo; Michael Christian; Sunarno Sunarno; Yustinus Yuniarto (JIEMS (Journal of Industrial Engineering and Management Systems), 2022)
A negative work environment can create work pressure for workers, including health professionals in hospitals. A collaborative work climate in the workplace contributes to one of the work environments. As a result, good cooperation among health professionals in hospitals can help to avoid work stress. This is because sustained work pressure can often contribute to the emergence of work stress. The purpose of this study is to determine and analyze whether the teamwork climate has a significant impact on stress recognition and job satisfaction. Furthermore, the purpose of this research is to determine and analyze the impact of stress recognition on job satisfaction. The purpose of this research is to determine whether stress recognition acts as a mediator between teamwork climate and job satisfaction. This quantitative study included 48 health professionals from Indonesian hospitals. The research data was analyzed with SMART PLS 3.0 and a PLS-SEM structural model. According to the findings of this study, teamwork climate has a significant effect on job satisfaction but not on stress recognition. The mere recognition of stress has no effect on job satisfaction. This study explains that stress recognition does not mediate the impact of teamwork climate on job satisfaction. Clarity of procedures and information is an important key in a hospital work environment for health professionals to be able to ask each other for certain conditions, especially those related to patient health and safety. Furthermore, to maintain organizational learning—continuous improvement, management must support all actions of workers in taking active actions that prioritize patient safety.